1995
DOI: 10.1302/0301-620x.77b4.7615604
|View full text |Cite
|
Sign up to set email alerts
|

Human meniscal transplantation. Preliminary results at 2 to 5-year follow-up

Abstract: In a prospective study, we evaluated the clinical results of 23 patients with a cryopreserved non-tissue-antigen matched meniscal transplant at a follow-up of from two to five years. These early results were satisfactory in 20 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
137
4
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(144 citation statements)
references
References 21 publications
2
137
4
1
Order By: Relevance
“…However, because the lateral meniscus plays a greater role in stress protection, a lateral meniscectomy can result in a painful knee more rapidly, leading to the higher number of knees treated with transplantation of a lateral meniscal allograft with a shorter mean follow-up time 2 . The overall rate of failure of the viable meniscal allografts in our study is consistent with previously published mediumterm and long-term data on deep-frozen and cryopreserved allografts fixed with a bone-plug or soft-tissue technique 4,5,7 . Our overall failure rate of 21% is, however, clearly lower than the failure rates of deep-frozen, irradiated allografts (failure rate, 44%) or lyophilized allografts 4,28 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, because the lateral meniscus plays a greater role in stress protection, a lateral meniscectomy can result in a painful knee more rapidly, leading to the higher number of knees treated with transplantation of a lateral meniscal allograft with a shorter mean follow-up time 2 . The overall rate of failure of the viable meniscal allografts in our study is consistent with previously published mediumterm and long-term data on deep-frozen and cryopreserved allografts fixed with a bone-plug or soft-tissue technique 4,5,7 . Our overall failure rate of 21% is, however, clearly lower than the failure rates of deep-frozen, irradiated allografts (failure rate, 44%) or lyophilized allografts 4,28 .…”
Section: Discussionsupporting
confidence: 91%
“…However, it cannot be concluded that a high tibial osteotomy should be performed in association with medial meniscal transplantation in a limb with normal axial alignment. Rather, it can be concluded that transplantation of a medial meniscal allograft in a varus-aligned knee should be combined with a high tibial osteotomy since varus malalignment is an absolute contraindication to transplantation of a medial meniscal allograft 5,18,[25][26][27][28] . Overall, twenty-one of the 100 viable allografts in our study failed at a mean of 5.4 ± 3.3 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most patients, some degree of joint space narrowing has to be expected but in some cases this narrowing is less than 1 mm [6]. In general, studies have demonstrated a trend of advancing cartilage deterioration overtime that correlates with MAT failure, even when cartilage lesions have been addressed with a cartilage-preserving procedure [10,75]. Although the majority of studies found no protective effect of MAT on knee cartilage [6,7,9], there are also several investigations both in animal models [76][77][78] and humans [31,33,73,75] reporting on the chondroprotective effects of MAT on knee cartilage.…”
Section: Osteoarthritismentioning
confidence: 99%